2015
DOI: 10.1371/journal.pone.0138358
|View full text |Cite
|
Sign up to set email alerts
|

Cough Aerosol Cultures of Mycobacterium tuberculosis: Insights on TST / IGRA Discordance and Transmission Dynamics

Abstract: RationaleThe diagnosis of latent tuberculosis (TB) infection (LTBI) is complicated by the absence of a gold standard. Discordance between tuberculin skin tests (TST) and interferon gamma release assays (IGRA) occurs in 10–20% of individuals, but the underlying mechanisms are poorly understood.MethodsWe analyzed data from a prospective household contact study that included cough aerosol culture results from index cases, environmental and contact factors. We assessed contacts for LTBI using TST and IGRA at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
3
13
0
Order By: Relevance
“…Conversely, in high prevalence settings, the expected proportion of contacts with TST conversion would be lower as a result of the opposite epidemiologic scenario. Interestingly, the proportion of contacts with TST conversion in the present study is consistent with the 4–10% reported in most other studies in both low and high TB burden settings [ 15 , 27 29 ]. The narrow variation in TST conversion across vastly different epidemiologic settings is striking in itself and unlikely to be explained by chance alone.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Conversely, in high prevalence settings, the expected proportion of contacts with TST conversion would be lower as a result of the opposite epidemiologic scenario. Interestingly, the proportion of contacts with TST conversion in the present study is consistent with the 4–10% reported in most other studies in both low and high TB burden settings [ 15 , 27 29 ]. The narrow variation in TST conversion across vastly different epidemiologic settings is striking in itself and unlikely to be explained by chance alone.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, there has been great interest in studying household contacts that remain uninfected despite close contact with a TB patient, as they are thought to represent a phenotype of innate or acquired resistance to M. tuberculosis infection [ 3 , 10 ]. In meta-analyses of household contact studies ~50% of contacts are found to be TST-negative [ 4 , 5 ], but this may be due to multiple factors such as exposure misclassification [ 29 ], missing TST converters, and limited sensitivity of TST and IGRA [ 3 ]. Our findings are in agreement with previous studies that found an association between TST conversion and socioeconomic status, [ 30 ] and lower rates of infection in females [ 27 ] –possibly as a result of family behavior patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high rate of disease progression among contacts could also result from a particularly aggressive MTB strain but, as noted above, our results do not support this. An alternative explanation is that the source cases had an intense cough and an unusually high bacterial burden and produced aerosols that delivered a large or repeated inoculum to their contacts [ 37 ]. It is also plausible that environmental conditions contributed to these outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…A hallmark symptom of active pulmonary tuberculosis and a major mechanism of disease transmission is a persistent, sometimes bloody cough. The vast majority of de novo Mycobacterium tuberculosis (Mtb) infections are acquired from contact with actively infected, coughing individuals (Fennelly et al, 2004;Jones-Ló pez et al, 2015). Previous hypotheses regarding the mechanism of cough in pulmonary tuberculosis emphasized the role of infection-induced lung irritation and production of inflammatory mediators (Turner, 2019;Turner and Bothamley, 2015).…”
Section: Introductionmentioning
confidence: 99%